Emerging therapy in arthritis: Modulation of markers of the inflammatory process. Issue 2 (8th January 2016) - Mortarino, P.A.; Goy, D.P.; Abramson, D.B.; Cabello, J.; Bumaguin, G.E.; Vitelli, E.J.; Toledo, J.; Sarrio, L.; Pezzotto, S.M.; Mardegan Issa, J.P.; Cointry, G.R.; Feldman, S.
ABSTRACT: The induction of tolerance has been proposed as a therapeutic strategy for arthritis aiming to decrease progression of the pathology, probably by promoting suppressor mechanisms of the autoimmune response. This work aimed to confirm whether the treatment with vitamin D3 could synergize oral tolerance induced by hydrolyzed collagen peptides, in our experimental model of antigen induced arthritis in New Zealand rabbits. Clinical observation of the phenomenon indicates that simultaneous treatment with hydrolyzed collagen peptides and vitamin D3 was beneficial when compared with no treatment, for arthritic animals, and for arthritic animals that received treatment with only hydrolyzed collagen peptides or vitamin D3. Treatment with hydrolyzed collagen peptides caused diminished proinflammatory cytokine levels, an effect synergized significantly by the simultaneous treatment with vitamin D3. The anatomical‐pathological studies of the animals that received both treatments simultaneously showed synovial tissues without lymphocytic and plasma cell infiltrates, and without vascular proliferation. Some of the synovial tissue of the animals of these groups showed a slight decrease in Galectin‐3 expression. We propose that simultaneous oral treatment with vitamin D3 and hydrolyzed collagen peptides could increase the immunoregulatory effect on the process of previously triggered arthritis. We used articular cartilage hydrolysate and not collagen II because peptides best expose antigenic determinants that could induce oral tolerance. Oral tolerance may be considered in the design of novel alternative therapies for autoimmune disease and we have herein presented novel evidence that the simultaneous treatment with vitamin D3 may synergize this beneficial effect. Microsc. Res. Tech. 79:89–97, 2016 . © 2016 Wiley Periodicals, Inc.